DECISION SUPPORT SYSTEM FOR SELECTING THE BEST EMPLOYEE AT PT BANK DIGITAL BCA USING SAW METHOD - Angga Ariyanto; Muhamad Ryansyah (JIKO (Jurnal Informatika dan Komputer), 2023)
The selection of the best employees is a long and complicated process. A person's  decision is bad because the employee selection process is based on subjectivity.  Therefore, we need a decision support system for the employee selection process. This  decision support system allows to determine the value of the calculation of all criteria.  The method used is Simple Additive Weighting (SAW). This method is a method for  finding the weighted sum. In the case study of determining the best employees at PT  Bank Digital BCA, there are four criteria, namely attendance, performance, assignment  discipline and approval. Each alternative (employee) will have these criteria. In this  case, to determine the best employee, we add the weight of the performance score for  each alternative to all the attributes. A larger value will indicate that the alternative is  more selected. In this case, the SAW method can determine the best employee based on  the highest score. Previously, PT Bank Digital BCA did not use the specified method  and criteria, it was also uncertain, after being tested with the established method and  determined criteria, the results were very good and appropriate. Thus this system is able  to handle the calculation of the best employee assessment at PT Bank Digital BCA so  that there will be no difficulty in determining the best employee.